Economic Effects of an Ocean Acidification Catastrophe - Colt, Stephen G.; Knapp, Gunnar P. (American Economic Review, 2016)
We assess the potential magnitude of the economic effects of an ocean acidification (OA) catastrophe by focusing on marine ecosystem services most likely to be affected. It is scientifically plausible that by 2200 OA could cause a complete collapse of marine capture fisheries, complete destruction of coral reefs, and significant rearrangement of marine ecosystems. Upper-bound values for losses from the first two effects range from 97 to 301 billion 2014 dollars per year (0.09 - 0.28% of current world GDP). We argue that aquaculture output would not be reduced, due to the high potential for adaptation by this young industry.